Dependensi Artificial Intelligence dan Kemampuan Analisis Kritis dalam Pembelajaran Pendidikan Pancasila - Hamsar Suci Amalia (Universitas Sains dan Teknologi Komputer, 2025)
Artificial Intelligence (AI) is an essential part of the learning process in college, especially about Pancasila Education learning. AI can facilitate and support students in independent learning. But using AI without sense of responsibility can reduce critical thinking skills, which is it can be affect student’s critical analysis abilities too. This research aims to analyse dependency AI associated with critical analysis abilities in Pancasila Education learning process, because Pancasila Education is not only contains theory, but also analysis and case studies. Research method used a qualitative method with a descriptive approach to present and understand the actual conditions or experienced by research subjects. All of data were collected by questionnaires and literature studies, then analysed through interpretation and description. The results of this research to contribute multidisciplinary studies and literature studies of education, especially critical analysis based subjects such as Pancasila Education. Therefore, it is important to implement simple regulations during learning process to minimise the bad effects of AI dependency.